Effectiveness of guided inquiry learning and self-regulated learning on students' numeracy skills - Mahsup; Syaharudin; Matthew Nepomuceno; Hasan bin Jali (Indonesian Journal of Educational Development (IJED), 2026)
Numeracy is a fundamental competency for university students, particularly in education-related programs. However, evidence shows that numeracy performance in Indonesia remains relatively low, highlighting the urgency of identifying effective instructional and learner-related factors that support numeracy development in higher education. Previous studies have often examined instructional approaches and learner characteristics separately, resulting in a limited understanding of their combined influence at the tertiary level. Therefore, this study aims to examine the influence of guided inquiry learning and self-regulated learning on students' numeracy skills. Using a quantitative correlational design, data were collected from 50 undergraduate students purposively selected from the Mathematics Education and Elementary Teacher Education programs. The inclusion criteria focused on students who had completed courses related to instructional strategies and mathematical reasoning. Data were obtained through validated Likert-scale questionnaires and analyzed using multiple linear regression. The results show that guided inquiry learning and self-regulated learning significantly predict numeracy skills (F = 96.923, p < .001). These findings indicate that numeracy development becomes more effective when inquiry-oriented instruction is supported by strong self-regulated learning capacities. Accordingly, this study recommends integrating guided inquiry learning with self-regulated learning strategies to strengthen numeracy competencies in higher education.